2017
DOI: 10.15576/gll/2017.4.79
|View full text |Cite
|
Sign up to set email alerts
|

Rural land management in Bangladesh: problems and prospects

Abstract: Based on a theoretical discussion from global perspective the paper describes present rural land administration and management structure in Bangladesh. Bangladesh is a land scarce country with high-density population. As most of the people live in rural areas and depend on agriculture and allied activities, proper rural land management is crucial. The paper presents an overall view of rural land management in Bangladesh and reveals that the current land management system is almost obsolete. Land administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The 1984 Land Reform Ordinance enacted a ceiling of future land acquisition to 51.9 hectares (21 acres), and sharecropping as the only admissible form of tenancy contract. In 1997, the Agricultural Khas Land and Settlement Policy was enacted to distribute khas land to the landless on a 99-year lease provision [41]. An investigation by Tariquzzaman and Rana [42] revealed that the process of acquiring khas land, being a political course rather than legal process, has been favouring more of the interests and benefits of the prevailing elites than others.…”
Section: Contemporary Land Laws and Regulationsmentioning
confidence: 99%
“…The 1984 Land Reform Ordinance enacted a ceiling of future land acquisition to 51.9 hectares (21 acres), and sharecropping as the only admissible form of tenancy contract. In 1997, the Agricultural Khas Land and Settlement Policy was enacted to distribute khas land to the landless on a 99-year lease provision [41]. An investigation by Tariquzzaman and Rana [42] revealed that the process of acquiring khas land, being a political course rather than legal process, has been favouring more of the interests and benefits of the prevailing elites than others.…”
Section: Contemporary Land Laws and Regulationsmentioning
confidence: 99%
“…The 1984 Land Reform Ordinance capped future land acquisition at 8.49 hectares (21 acres) and established sharecropping as the only acceptable form of tenancy contract. In 1997, the Agricultural Khas Land and Settlement Policy was enacted to distribute khas land to the landless on 99-year leases [47]. An investigation by Tariquzzaman and Rana [48] revealed that, as a political act rather than a legal one, the process determining the acquisition of khas land has favored the interests of the prevailing elites.…”
Section: Contemporary Land Laws and Regulationsmentioning
confidence: 99%
“…Land provides humanitarian assistance and, at the same time, expedites activities necessary for one’s livelihood. In many developing countries, land is the symbol of power to people in both urban and rural areas (Masum 2017 ). Hence, corruption around the world is most often related to land corruption.…”
Section: Literature Reviewmentioning
confidence: 99%